The Influence of Self-Efficacy, School Environment, and Peers on the Learning Outcomes of Eleventh-Grade Students Thru Learning Discipline and Learning Interest as Intervening Variables in Economics Subjects - Welya Azrianti; Stevani; Rika Verawati (Global Action and Education for Society, 2025)
This study aims to analyze the influence of self-efficacy, school environment, and peer relationships on the academic achievement of eleventh-grade students at SMAN 3 Bukittinggi, with study discipline and learning interest as intervening variables. The research employs a quantitative approach with a population of 86 students, utilizing total sampling techniques and a closed questionnaire as the instrument. Data analysis is conducted through path analysis and hypothesis testing using the t-test. The results indicate that: (1) self-efficacy significantly affects academic achievement; (2) the school environment significantly affects academic achievement; (3) peer relationships significantly affect academic achievement; (4) study discipline does not significantly affect academic achievement; (5) learning interest significantly affects academic achievement; (6) self-efficacy, school environment, and peer relationships significantly influence both study discipline and learning interest; (7) learning interest significantly affects study discipline. Thus, the intervening variables (study discipline and learning interest) strengthen most of the effects of the independent variables on academic achievement.